UJI KORELASI DAN REGRESI ADAPTASI GANDUM (Triticum Aestivum L.) DI DATARAN TINGGI SUKARAMI SOLOK SUMATERA - M Nizar Hanafiah Nasution; Irwati Chaniago; Auzar Syarif (Fakultas Pertanian Universitas Muhammadiyah Tapanuli Selatan, 2018)
Research on the adaptation grain ( Triticum aestivum L. ) at a high altitude sukarami Solok West Sumatra. This study attempts to compare growth and production of several galur grain at environment tropics. Research done by experimental methods shelves ( draft random ) group with 9 treatment galur and 3 group. Nine furrow that sukarami all galur give impact on every variable responnya except on the long panicles and the number of per panicles ears. Sukarami most adaptive strain H-20. Key words: growth, production, galur, tropics